2020
DOI: 10.1111/1744-9987.13566
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged shedding of SARS‐CoV‐2 in COVID‐19 infected hemodialysis patients

Abstract: An outbreak of coronavirus disease 2019 , now known to be caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), that began in China in December 2019, has since spread rapidly throughout the world. 1 There are several reports of hemodialysis patients with COVID-19. [2][3][4] Hemodialysis patients appear to be a population at high risk for severe COVID-19, because factors identified as risk factors for severe COVID-19 are often present in these patients: old age, hypertension, cardiovascular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Nasal shedding of SARS-CoV-2 was detected in 41% of patients by day 15 following the initial positive swab [ 100 ]. On average shedding of viral particles lasted 15.1–29 days in infected patients on HD [ 135 , 139 ]. Two studies reported that HD patients tested positive for SARS-CoV-2 RNA on repeated testing despite being negative on two prior consecutive nasopharyngeal swabs [ 138 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nasal shedding of SARS-CoV-2 was detected in 41% of patients by day 15 following the initial positive swab [ 100 ]. On average shedding of viral particles lasted 15.1–29 days in infected patients on HD [ 135 , 139 ]. Two studies reported that HD patients tested positive for SARS-CoV-2 RNA on repeated testing despite being negative on two prior consecutive nasopharyngeal swabs [ 138 , 140 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the former two issues are of easy resolution, discontinuing transmission-based precautions for HD patients relies on more complex underpinnings. The immune-suppressed HD patients may shed the virus longer than previously recognized [ 139 ]. Given the evolving recommendations on the criteria for discontinuing isolation [ 157 , 158 ], may be prudential to consider HD patients as immuno-compromised and await the resolution of nasal shedding before de-isolating these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these patients also show impaired antiviral immune responses because of their impaired kidney functions. Hemodialysis patients with COVID-19 reportedly have a poor prognosis [5][6][7][8][9]. In the present study, we examined the clinical characteristics of hemodialysis patients with COVID-19 during the 6th wave of infection at our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these patients also have impaired antiviral immune responses because of their impaired kidney functions. Numerous reports of hemodialysis patients with COVID-19 have been published [2][3][4][5][6][7][8][9]; however, the usual clinical course of hemodialysis patients with COVID-19 remains unclear. We examined data from hemodialysis patients with COVID-19 at our hospital and report the differences between patients with critical and noncritical disease severity.…”
Section: Introductionmentioning
confidence: 99%